Anaerobic fungi (phylum Neocallimastigomycota): advances in understanding their taxonomy, life cycle, ecology, role and biotechnological potential. Issue 1 (11th August 2014) - Gruninger, Robert J.; Puniya, Anil K.; Callaghan, Tony M.; Edwards, Joan E.; Youssef, Noha; Dagar, Sumit S.; Fliegerova, Katerina; Griffith, Gareth W.; Forster, Robert; Tsang, Adrian; McAllister, Tim; Elshahed, Mostafa S.
Abstract Anaerobic fungi (phylum Neocallimastigomycota) inhabit the gastrointestinal tract of mammalian herbivores, where they play an important role in the degradation of plant material. The Neocallimastigomycota represent the earliest diverging lineage of the zoosporic fungi; however, understanding of the relationships of the different taxa (both genera and species) within this phylum is in need of revision. Issues exist with the current approaches used for their identification and classification, and recent evidence suggests the presence of several novel taxa (potential candidate genera) that remain to be characterised. The life cycle and role of anaerobic fungi has been well characterised in the rumen, but not elsewhere in the ruminant alimentary tract. Greater understanding of the 'resistant' phase(s) of their life cycle is needed, as is study of their role and significance in other herbivores. Biotechnological application of anaerobic fungi, and their highly active cellulolytic and hemi‐cellulolytic enzymes, has been a rapidly increasing area of research and development in the last decade. The move towards understanding of anaerobic fungi using –omics based (genomic, transcriptomic and proteomic) approaches is starting to yield valuable insights into the unique cellular processes, evolutionary history, metabolic capabilities and adaptations that exist within the Neocallimastigomycota.